Determinants of Access to Credit by Maize (Zea mays) Farmers in Southern Taraba, Taraba State, Nigeria - Asani, B. C.; Ukpe, U. H.; Filli, F. B (Kwaghe International Journal of Engineering and Information Technology, 2025)
This study investigates the determinants of access to credit among maize farmers in Southern Taraba, Taraba State, Nigeria. The specific objectives were to identify the constraints hindering credit acquisition and to assess the key factors influencing farmers’ access to credit. A multi-stage sampling procedure was employed to collect primary data from 180 respondents using structured questionnaires. Data analysis involved both descriptive and inferential statistical methods. The findings revealed that major constraints to credit access included complex application procedures, high interest rates, lack of collateral, short repayment periods, delayed fund disbursement, and limited awareness of available credit sources. Key determinants influencing access to credit were identified as ownership of collateral, marital status, income level, farm size, and age. Based on these findings, the study recommends that policymakers prioritize improving rural farmers’ access to information, extension services, and agricultural insurance to address demand-side barriers. Additionally, institutional capacity building for both lenders and borrowers should be integrated into all credit programs to enhance credit uptake, increase agricultural productivity, and improve farmer incomes. Credit policy interventions should be tailored to the specific needs and constraints of farming households.